ANALISIS FAKTOR PENYEBAB KECELAKAAN LALU LINTAS PENGENDARA SEPEDA MOTOR: UPAYA MENINGKATKAN KESELAMATAN BERKENDARA - Fadhil, Ammar; Muliani, Fitri; Munandar, Aris (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2024)
Traffic accidents are one of the major challenges faced by many countries, especially in areas with high vehicle density, such as Aceh. Each year, the number of vehicles continues to grow, resulting in thousands of fatalities and many others suffering injuries that significantly affect their quality of life. This study focuses on analyzing one of the factors contributing to traffic accidents among motorcycle riders in Bireuen Regency. Data was collected using a self-reporting method through questionnaires distributed to 250 respondents and analyzed using multiple regression to determine the relationships between variables. The study found that, based on rider perceptions, the